Gender and diversity at school and their interface in teacher education: The experience of GDE/UFPB - Silva, Jeane Felix da (2023)
This paper focuses on the Gender and Diversity at School (GDE) program, a pioneering nationwide teacher continual education policy proposal. Initially, it places this initiative in the current Brazilian political context. It then presents the experience of its first class, sponsored by the Interdisciplinary Gender Center (NIPAM) of the College of Education of the Federal University of Paraiba (UFPB), in 2014-2015. Mainly, it addresses the recent experience of its second class, in 2020-2021, through distance education, during the social isolation resulting from the Covid-19 pandemic. Based on responses to a questionnaire applied in July 2021, it describes its students’ motivations and expectations. At this time of attack on gender studies and policies, especially in schools, it concludes by arguing the importance of including the gender perspective in teacher education.